Comparison of Characteristics of Suicide Attempts Registered in Urban and Rural Areas in China - Li, Lingling; Liu, Chunxu; Tong, Yongsheng; Wu, Jianlan; Zhou, Wei; Yin, Yi; Wu, Mengjie; Tong, Ruoyang; An, Jing (Frontiers in Psychiatry, 2022)
Objective: To compare the characteristics of suicide attempts registered in general hospitals in urban and rural areas in China. Methods: From January 2007 to December 2011, suicide attempts registered in hospitals in five rural counties and in Beijing Municipality were included. Univariate and multivariate analysis were used to compare the characteristics of rural and urban suicide attempts in China. Results: A total of 5515 episodes of suicide attempts were included, 1966 (35.6%) of them were from rural counties and 3549 (64.4%) were from Beijing. Compared with urban counterparts, the rural suicide attempters had lower proportion of females (61.9% v 72.3%), more likely reporting previous suicide attempt history (56.9% v 16.4%) and staying in hospital more than one day (81.5% v 44.6%). The most common methods of suicide attempts were pesticides ingestion in rural areas (52.1%) and taking medications in urban area (39.2%). Results of multivariate analysis indicated that, suicide attempt registered in rural areas, pesticide ingestion, and previous suicide attempts history were associated with longer treatment in hospitals. Conclusions: Suicide attempts registered in rural areas were different from those in urban areas in China. It is essential to improve the equipments and ability of medical resuscitation for pesticide ingestion in rural hospitals in China.